Exploring the Potential of Cashew Nutshells: A Critical Review of Alternative Applications (2024)
The production of cashew nuts has been increasing globally, leading to a greater volume of waste materials that require proper management. Nevertheless, cashew nutshells (CNS), currently considered waste by most processors, offer a noteworthy opportunity for alternative applications owing to their distinct physical, chemical, and thermal properties. This article reviews alternative applications for CNS that can leverage these properties, while evaluating research gaps. The potential uses are classified into three categories: material development, energy production, and substance absorption. In the materials segment, various examples are discussed where CNS serves as raw material to synthesize biopolymers, cementitious materials, and a broad range of composites. The energy production section discusses various processes that utilize CNS, including pyrolysis, gasification, and briquette production. The absorption section presents CNS and activated carbon derived from CNS as effective absorbents for liquid-phase and gas-phase applications. While this review highlights numerous research-level possibilities for CNS utilization, only a few of these options have been implemented within the industry. Consequently, further research is essential, particularly in CNS characterization, economic and environmental assessment, and real-life implementation, to broaden and enhance the integration of this biomass into applications that can contribute to the value of both its production and processing chain.